The Effect of Project in Problem-Based Learning on Students’ Scientific and Information Literacy in Learning Human Excretory System - Siti Juleha; Ikmanda Nugraha; Selly Feranie (Journal of Science Learning, 2019)
The present study aims to investigate the effect of Project in Problem-Based Learning on students’ scientific and information literacy in grade 8 studying in one of the private schools in Bandung in the human excretory system topic. A sample of 39 students in two classes was selected purposively from the five classes available in the school. An experimental group comprising 19 students received the instruction by Problem-Based Learning with the project at the end of the lesson while the control group comprising 20 students received the human excretory instruction by using Problem-Based Learning without a project. The data was collected via the pre-test and post-test administration. The results were statistically analyzed using SPSS software by employing an independent t-test. Results indicated that after the one-month treatment period, students in the experimental group have a higher score in the scientific literacy test compared to the students in the control group even it was not significantly different. Therefore, the results of students’ information literacy showed that there was a significant difference between the experiment and control group. It is concluded that Project in problem-based learning is useful to conduct as the learning strategies in the classroom to improve students’ scientific and information literacy.